A comprehensive overview on osteoporosis and its risk factors - Pouresmaeili F; Kamalidehghan B; Kamarehei M; Goh YM (Dove Medical Press, 2018)
Farkhondeh Pouresmaeili,1,2 Behnam Kamalidehghan,2,3 Maryam Kamarehei,4 Yong Meng Goh51Infertility and Reproductive Health Research Center (IRHRC), Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Medical Genetics Department, Faculty of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Medical Genetics Center, National Institute of Genetics Engineering and Biotechnology (NIGEB), Tehran, Iran; 4Department of Biochemistry and Biophysics (IBB), University of Tehran, Tehran, Iran; 5Department of Veterinary Preclinical Sciences, Faculty of Veterinary Medicine, Universiti Putra Malaysia (UPM), Serdang, Malaysia Abstract: Osteoporosis is a bone disorder with remarkable changes in bone biologic material and consequent bone structural distraction, affecting millions of people around the world from different ethnic groups. Bone fragility is the worse outcome of the disease, which needs long term therapy and medical management, especially in the elderly. Many involved genes including environmental factors have been introduced as the disease risk factors so far, of which genes should be considered as effective early diagnosis biomarkers, especially for the individuals from high-risk families. In this review, a number of important criteria involved in osteoporosis are addressed and discussed.Keywords: atherosclerosis, hyperparathyroidism (HPT), bone and hip fractures, bone mineral density (BMD)